A First 2 MW-Class (136)/170/204 GHz Multi-Frequency Gyrotron Pre-Prototype for DEMO: Design, Construction and Key Components Verification - Ruess, Tobias (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2023)
A gyrotron is used in magnetically confined plasma experiments for heating, current drive, plasma stabilization and plasma diagnostics. This work presents the first design and construction of a multi-frequency / multi-purpose coaxial-cavity pre-prototype gyrotron operating at (136)/170/204 GHz with an output power of 2 MW. It is the first step towards operating frequencies up to 240 GHz using the coaxial-cavity gyrotron technology.